A stratégiai alapú integrált emberi erőforrás gazdálkodás bevezetése action learning módszerekkel = Introduction of the strategy-based, integrated human resource management system by action learning methods - Stréhli-Klotz Georgina (Taylor : gazdálkodás- és szervezéstudományi folyóirat, 2016)
This study aims to demonstrate the current state of public service, covering in particular currently used human resource management methods additionally the new opportunities of innovative competence development solutions which combine the tools used in management trainings and reasons of the introduction of new strategic-based HR system. This paper summarizes the basic principles of the strategy-based, integrated human resource management system, covers the more accepted theories of the public service human resource management system. One of them is the action learning technique, which this study discusses in detail while it seeks to ascertain in what form the new methodology can become an integral part of the Hungarian public service development, especially in the field of competence-based leadership development.